Magnetic Microtweezers: A Tool for High‐Throughput Bioseparation in Sub‐Nanoliter Droplets. Issue 1 (27th July 2022) - Dumas, Simon; Richerd, Mathilde; Serra, Marco; Descroix, Stéphanie
Abstract: Droplet microfluidics has revolutionized the field of single‐cell analysis. Production of micro‐droplets at high throughput allows for rapid isolation of single cells within micro‐compartments, which are then subjected to different analytical processes. However, certain operations, such as physical separation from droplets, remain difficult to implement at high throughput and single‐cell level but would be highly valuable to currently expanding multiomics techniques, where several biomolecular modalities are involved. This work presents a method based on microfabricated NiFe structures, the magnetic microtweezers, to trap and extract magnetic particles from a continuous stream of sub‐nanoliter droplets, and enable physical separation from single cell‐based droplets. Using a physical model, simulations, and experiments, a comprehensive description of the complex particle extraction process is provided. After optimization, the magnetic microtweezers provided unprecedented particle extraction performance, allowing extraction of high loads (10‐20 ng) of magnetic particles from 500 pL droplets, with a capture rate close to 100% at 20 Hz. To evaluate the applicability to single‐cell analysis, mRNA extraction is performed. It demonstrated around 72% specific recovery of mRNA from droplets containing purified nucleic acids, and 43% from single cells. Overall, this approach enables efficient physical separation that is compatible with existing high‐throughput droplet‐based single‐cell workflows. Abstract : Droplet microfluidics is today a major technology for single‐cell analysis. Despite recent advances, there is still a high demand for physical extraction methods within sub‐nanoliter droplets, especially for multiomic studies. This paper presents an original approach, based on electroplated magnetic microstructures, to extract functionalized magnetic beads from sub‐nanoliter droplets at high‐throughput, and shows its applicability for bioseparation at single‐cell level.